Pain Level and Prostaglandin-E2 using Counter-Pressure During 1st Stage of Labor - Sri Rejeki; Ariawan Soejonoes; Soenarjo Soenarjo; Amin Husni (Jurnal Ners, 2014)
Introduction : Increased the forming of PG-E2 able to trigger uterus contraction and cause of labor pain. The longer a woman experiences with labor pain the more dangerous for the mother and the baby. So, it is necessary the solutions for labor pain problem. Some studies reported that giving some medicines to relieve the pain often have many side effects on fetus. It is necessary to fi nd a method which is not only effective but also has minimal side effect and it doesn’t affect on uterus contraction and labor progression. Counter-Pressure become preferences to reduce labor pain. The purpose of this study is to analyze Counter-Pressure in relieving the labor pain. The labor pain level, PG-E2 level become the indicators of this study. Methods: This study was quasi-experimental designs, by using a Nonequivalent Control group Design. As many as 52 primigaravidas in labor progression phase I, with consecutive sampling were chosen as samples. They were divided into 2 groups; 26 subjects with counter-pressure treatment and 26 subjects as control. Result: There were a very signifi cant decline of labor pain phase I level on counter-pressure treatment (p=0.000)). There was no change of PG-E2 level on the counter pressure treatment (p=0,095), but there is change on control.Conclusion: Counter-pressure method is very signifi cant in declining the labor pain level. Counter-pressure method do not affect both the PG-E2.